The Islamic Ruling on Women Holding Judicial Positions: A Comparative Jurisprudential Study (Journal of the College of Basic Education, 2026)
This research explores the Islamic ruling on women assuming judicial positions, through a comparative juristic study of the views of Islamic schools of thought and some contemporary scholars. The legal evidence for each opinion is presented and discussed in light of the objectives of Sharia and modern realities. The study concludes that absolute prohibition is not supported by definitive evidence, and that conditional permissibility is more aligned with achieving public interest. The research adopts a comparative jurisprudential methodology based on analysis and evaluation.